Recreating van der Wielen and de Groot’s (2019) thermocasted Paraloid™ B-72, with a twist. - Loubser, Maggi (University of Pretoria, 2025)
Mini Dissertation (MSocSci (Cultural Heritage Studies: Heritage Conservation))--University of Pretoria, 2024.